Influence of yeast strain, extended lees contact and nitrogen supplementation on glutathione concentration in wine. (6th May 2013) - Kritzinger, E.C.; Bauer, F.F.; Du Toit, W.J.
Abstract Background and Aims Glutathione (GSH) is an antioxidant that plays several important roles in wine, including the limitation of browning and of atypical ageing off‐flavours and the preservation of important varietal aroma compounds. In finished wines, however, GSH concentration varies significantly. The influence of several oenological factors, including yeast strain, extended lees contact and yeast assimilable nitrogen content, on the concentration of GSH in wine and in a model wine has been investigated. Methods and Results The influence of 20 commercial Saccharomyces cerevisiae wine yeast strains on the GSH content after alcoholic fermentation was evaluated in a chemically defined grape juice (CDGJ). A significant difference was observed between strains, with some strains resulting in a GSH content sevenfold higher than that of other strains. In Sauvignon Blanc grape juice with a range of initial GSH concentration, the concentration of GSH fluctuated during fermentation. After alcoholic fermentation, however, GSH concentration was generally lower than that initially present in the juice; strains that resulted in the highest GSH concentration in the wines prepared from CDGJ did not necessarily display a similar trend in grape juice. Conclusions Yeast strains have a significant impact on the GSH concentration in finished wines, but specific outcomes are dependent on as yet unknown environmental factors. Yeast assimilable nitrogen concentration in a CDGJ did not impact on GSH concentration after fermentation, and GSH concentration generally decreases during ageing irrespective of the yeast strain or the presence of lees. Significance of the Study The data highlight the influence of certain vinification practices on the GSH concentration in wine and suggest strategies to increase the GSH concentration in commercial wines. Such strategies may help to reduce the use of sulfur dioxide by the industry.